MiR181b is induced by the chemopreventive polyphenol curcumin and inhibits breast cancer metastasis via down‐regulation of the inflammatory cytokines CXCL1 and ‐2. Issue 3 (16th January 2014) - Kronski, Emanuel; Fiori, Micol E.; Barbieri, Ottavia; Astigiano, Simonetta; Mirisola, Valentina; Killian, Peter H.; Bruno, Antonino; Pagani, Arianna; Rovera, Francesca; Pfeffer, Ulrich; Sommerhoff, Christian P.; Noonan, Douglas M.; et al.
Abstract : Chronic inflammation is a major risk factor for the development and metastatic progression of cancer. We have previously reported that the chemopreventive polyphenol Curcumin inhibits the expression of the proinflammatory cytokines CXCL1 and ‐2 leading to diminished formation of breast and prostate cancer metastases. In the present study, we have analyzed the effects of Curcumin on miRNA expression and its correlation to the anti‐tumorigenic properties of this natural occurring polyphenol. Using microarray miRNA expression analyses, we show here that Curcumin modulates the expression of a series of miRNAs, including miR181b, in metastatic breast cancer cells. Interestingly, we found that miR181b down‐modulates CXCL1 and ‐2 through a direct binding to their 3′‐UTR. Overexpression or inhibition of miR181b in metastatic breast cancer cells has a significant impact on CXCL1 and ‐2 and is required for the effect of Curcumin on these two cytokines. miR181b also mediates the effects of Curcumin on inhibition of proliferation and invasion as well as induction of apoptosis. Importantly, over‐expression of miR181b in metastatic breast cancer cells inhibits metastasis formation in vivo in immunodeficient mice. Finally, we demonstrated that Curcumin up‐regulates miR181b and down‐regulates CXCL1 and ‐2 in cells isolated from several primary human breast cancers. Taken together, these data show that Curcumin provides a simple bridge to bring metastamir modulation into the clinic, placing it in a primary and tertiary preventive, as well as a therapeutic, setting. Highlights: We show that Curcumin modulates expression of miR181b. We show that miR181b overexpression inhibits breast cancer cell growth and invasion. We show that miR181b modulates CXCL1 and ‐2, resulting in reduction of metastases. Our data allow the introduction of metastamirs into the clinic. Our data provide evidence for the use of curcumin for cancer prevention.